2006
DOI: 10.1111/j.1468-3083.2006.01748.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of narrow‐band UVB phototherapy on cutaneous microbiota of children with atopic dermatitis

Abstract: The results of the present study show the beneficial effect of UVB phototherapy on AD and suggest that this may be attributable not only to reduction of skin surface bacteria but also to the suppression of superantigen production from S. aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 24 publications
2
52
0
3
Order By: Relevance
“…Previous studies have shown that more than 50-60% of Staph. aureus strains isolated from patients with AD are exotoxin-producing strains, which can secrete various exotoxins including SEA, SEB, SEC, SED and TSST-1 (Bunikowski et al 2000;Chen et al 2005;Silva et al 2006;Schlievert et al 2008;Nada et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that more than 50-60% of Staph. aureus strains isolated from patients with AD are exotoxin-producing strains, which can secrete various exotoxins including SEA, SEB, SEC, SED and TSST-1 (Bunikowski et al 2000;Chen et al 2005;Silva et al 2006;Schlievert et al 2008;Nada et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, UVA1 irradiation seems to be superior to conventional UVA-UVB phototherapy in patients with severe AD 85,86 . Narrow-band UVB alone is also effective and its activity seems to be partially due to a decrease in the microbial colonization 87 .…”
Section: ) Phototherapymentioning
confidence: 99%
“…7 Impetiginized atopic skin can even improve on UV exposure without antibacterial treatment. 8 Hence, the question arises how UV radiation, which is known to be immunosuppressive, does not generally worsen but sometimes even improves bacterial infections.…”
mentioning
confidence: 99%